2021
DOI: 10.3390/molecules26154572
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Microfiltration Membranes Modification by Supercritical Solvent Impregnation—Potential Application in Open Surgical Wound Ventilation

Abstract: This study investigated supercritical solvent impregnation of polyamide microfiltration membranes with carvacrol and the potential application of the modified membranes in ventilation of open surgical wounds. The impregnation process was conducted in batch mode at a temperature of 40 °C under pressures of 10, 15, and 20 MPa for contact times from 1 to 6 h. FTIR was applied to confirm the presence of carvacrol on the membrane surface. In the next step, the impact of the modification on the membrane structure wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
1
1
Order By: Relevance
“…Overall, satisfactory impregnation yields (7.22-10.57 wt.%) were achieved for all the samples at the studied conditions. Nevertheless, these impregnation yields were lower than the reported for carvacrol in other polymers such as cellulose acetate films (31 wt.%) [52] and polyamide membranes (40 wt.%) [53] using similar processing conditions, which evidence the low chemical affinity between carvacrol and PCL. Interestingly, the reported impregnation yield of thymol (14.8 wt.%) in pure PCL [20] was considerably higher than the obtained in this study for carvacrol in the pure PCL scaffolds using very similar processing conditions (7.22-7.71 wt.%), even considering the great chemical similarity between both phenolic compounds.…”
Section: Effect Of Ha Content Temperature and Depressurization Rate O...contrasting
confidence: 56%
“…Overall, satisfactory impregnation yields (7.22-10.57 wt.%) were achieved for all the samples at the studied conditions. Nevertheless, these impregnation yields were lower than the reported for carvacrol in other polymers such as cellulose acetate films (31 wt.%) [52] and polyamide membranes (40 wt.%) [53] using similar processing conditions, which evidence the low chemical affinity between carvacrol and PCL. Interestingly, the reported impregnation yield of thymol (14.8 wt.%) in pure PCL [20] was considerably higher than the obtained in this study for carvacrol in the pure PCL scaffolds using very similar processing conditions (7.22-7.71 wt.%), even considering the great chemical similarity between both phenolic compounds.…”
Section: Effect Of Ha Content Temperature and Depressurization Rate O...contrasting
confidence: 56%
“…Our previous studies demonstrated that it was possible to modify commercial polyamide and cellulose acetate microfiltration membranes by impregnation in scCO 2 with thymol and carvacrol as antibacterial agents [4,27,28] . The active substance loadings over 30% were possible without membranes microstructure disturbance.…”
Section: Introductionmentioning
confidence: 99%